Digital Transformation of Islamic Universities for Lecturer Performance Based on Decision Support System - Nurohman, Muhamad; Andriyani, Widyastuti; Redjeki, Sri (QUALITY, 2024)
Digital Transformation of Islamic Universities for Lecturer Performance Based on Decision Support System. The research offers the utilization of digital transformation along with the development of information and communication technology today needs to be done to improve the quality of education, especially in Islamic universities, one of which is the existence of various systems to support them with the existence of multiple kinds of systems to support decision making or Decision Support System. The system for determining outstanding lecturers is used to support learning and teaching activities on campus to create qualified and competent students in their fields. STAINU Purworejo is an Islamic university located in Central Java Province which has been established since 1974 and has 33 lecturers. The process of determining outstanding lecturers that is still running at STAINU Purworejo campus still has shortcomings, namely requiring a long time to process questionnaire data that has been distributed to the campus community and the decision results obtained are not fully valid and not objective. The determination of outstanding lecturers has five assessment criteria, namely: student assessment, superior assessment, educational qualifications, published journals, and lecturer administration. The method used is the Analytical Hierarchy Process (AHP) method to calculate the weight of each criterion and the Technique for Order by Similarity to Ideal Solution (TOPSIS) to rank alternatives based on each criterion. Based on calculations carried out using a combination of AHP and Topsis and system implementation, the highest preference value is 0.835 and the lowest preference value is 0.27. From the results of these calculations, it can be concluded that the utilization of digital transformation for lecturer performance with a Decision Support System that utilizes a combination of AHP and TOPSIS methods can be used to help provide recommendations in decision-making to determine the best lecturer at the Nahdlatul Ulama Islamic Religious College (STAINU) Purworejo.